Prosodic Means of Speech Influence Realization: Auditory Analysis - Tomakhiv, Marta (East European Journal of Psycholinguistics, 2017)
The article offers the results of the experimental phonetics research on the role of intonation in speech influence realization in the video lecture as a main massive open online courses material. This methodology is elaborated according to the proven techniques in contemporary phonetics and combines the use of auditory analysis, methods of quantitative data and linguistic analysis, methods of semantic differential and questionnaire. The goal of the experiment was to prove the hypothesis about the role of prosodic organization and components of the tutors’ intonation in video lectures in better supporting students’ attention, capturing the interest to the subject, facilitating understanding, which help in realization of speech influence in scholarly discourse, thus making the communication and learning more efficient, productive and successful. As a result of the experiment, the intonation parameters used in the video lecture and contributory for students’ perception have been established. The paper gives brief insights into such notions as speech influence, scholarly discourse and an e-lecture as a genre of modern scholarly discourse. References Антошинцева М. А. Механизмы адаптации жанра научно-учебной лекции к электронной сфере коммуникации. [Електронний ресурс]. Режим доступу: www.cyberleninka.ru/article/n/mehanizmy-adaptatsii-zhanra-nauchno-uchebnoy-lektsiik-elektronnoy-sfere-kommunikatsii Antoshyntseva, M. A. Mekhanizmy adaptatsii zhanra nauchno-uchebnoy lektsii k elektronnoy sfere kommunikatsii. [Mechanisms of scientific and academic discourse genre adaptation to the electronic domain of communication]. Retrieved from: www.cyberleninka.ru/article/n/mehanizmy-adaptatsii-zhanra-nauchno-uchebnoy-lektsiik-elektronnoy-sfere-kommunikatsii Валігура О. Р. Фонетична інтерференція в англійському мовленні білінгвів: монографія. Тернопіль: Підручники і посібники, 2008. Valihura, O. R. (2008). Fonetychna Interferentsiia v Anhliiskomu Movlennia Bilinhviv. [Phonetical Interference in the English Speech of the Bilinguals]. Ternopil: Pidruchnyky i Posibnyky. Калита А. А. Энергетика речи: монография. К.: Кафедра, 2016. Kalyta, A. A. (2016). Energetika Rechi [Speech Energetics]. Kyiv: Kafedra. Калита А. А. Актуалізація емоційно-прагматичного потенціалу висловлення: монографія. Тернопіль: Підручники і посібники, 2007. Kalyta, A. A. (2007). Aktualizatsia Emotsiino-Prahmatychnoho Potentsialu Vyslovlennia. [Emotional and Pragmatic Potential of the Utterance Actualization]. Ternopil: Pidruchnyky i Posibnyky. Каспаринський О. Ф., Полянская Е. И. Видеолекция как жанр. [Електронний ресурс]. Режим доступу: https://istina.msu.ru/media/publications/articles/ 8e9/82a/ 3559014/29LINK_FOK13v07.pdf Kasparinskyi, O. F., Polianskaia, E. I. Videolektsiia kak Zhanr. [Videolecture as a Genre]. Retrieved from: https://istina.msu.ru/media/publications/articles/8e9/т82a/ 3559014/29LINK_FOK13v07.pdf. Osgood, C. E., Suci, G. C. and Tannenbaum, P. H. (1957). The Measurement of Meaning. Urbana, IL : University of Illinois Press. Падалка О. В. Просодика комунікативного членування промов сучасних політичних діячів Німеччини (експериментально-фонетичне дослідження): дисертація кандидата філологічних наук: 10.02.04 / Ольга Володимирівна Падалка. Київ: КНЛУ, 2015. Padalka, O. V. (2015). Prosodyka Komunikatyvnoho Chlenuvannia Promov Suchasnykh Politychnukh Diiachiv Nimechchyny (Eksperymentalno-Fonetychne Doslidzhennia). Ph.D. dissertation [Prosody of the Communicative Segmentation of Speech of Contemporary German Politicians (Experimental Phonetics Research)]. Kyiv: Kyiv National Linguistic University. Peer, W. Van, Hakemulder, F., Syngier, S. (2012). Scientific Methods for the Humanities. (Linguistic Approaches to Literature). Amsterdam: John Benjamins. Рубчак О. Б. Просодична організація англомовних інтерв’ю (експериментальнофонетичне дослідження): Дис. ... канд. філол. наук: 10.02.04. Київ: КНЛУ, 2015. Rubchak, O. B. (2015). Prosodychna Organizatsiia Anhlomovnykh Interviu (Eksperymentalno-Fonetychne Doslidzhennia). Ph.D. dissertation [Prosodic Structure of the English Interviews (Experimental Phonetics Research)]. Kyiv: Kyiv National Linguistic University. Седов К. Ф. Нейропсихолингвистика. Москва: Лабиринт, 2007. Sedov, K. F. (2007). Neiropsikholingvistika. [Neuropsycholinguistics]. Moscow: Labirint. Селіванова О. О. Мовленнєвий вплив у комунікативній взаємодії // Психолінгвістика. 2012. № 10. С. 223–229. Selivanova, O. (2012). Movlennievyi Vplyv u Komunikatyvnii Vzaiemodii. Psykholinhvistyka, 10, 223–229. Demetriadis, S., Pombortsis, A. E-Lectures for Flexible Learning: a Study on their Learning Efficiency. Retrieved from: http://www.ifets.info/journals/10_2/13.pdf Tomakhiv, M. (2016). E-Lecture as a new genre of scholarly discourse. Science and Education a New Dimension. Philology, IV (23), 100, 80–83. Trench Brian. Internet − turning science communication inside‐out? Retrieved from: http://doras.dcu.ie/14807/1/internet_science_communication.pdf